Integration and expression of hmgr 1 gene in the transgenic plants of Hevea brasiliensis (clone RRII 105) - Jayashree R (PLACROSYM XXI. International Symposium on Plantation Crops, 10-12 December 2014, Kozhikode, India, pp. 52. Abstracts.)
In Hevea brasiliensis, natural rubber (cis-1, 4-polyisoprene) is produced in the milky cytoplasm of specialized cells called laticifers. The enzyme 3-hydroxy 3-methylglutaryl Coenzyme A reductase (HMGR) catalyzes the first step in the isoprenoid pathway and is considered as a rate limiting enzyme in rubber biosynthesis. Agrobacterium mediated genetic transformation of the embryogenic tissues of zygotic origin using the plasmid vector pBIBhmgr 1 oroduced transgenic plants. The integration of the transgene was confirmed in the plants using southern hybridization. The expression of the transgene was studied in the plants using northern analysis. Higher transcript level was observed in the tested plant compared to the control. The HMGR protein was semi-quantified in the selected transgenic plants using ELISA, where a 2-8 fold increase in the HMGR enzyme activity was noticed. After correlating the HMGR activity with the latex yield in Hevea brasiliensis, this protein parameter can be used as a molecular tool for the early selection of plants in Hevea breeding programmes.
Keywords: Agrobacterium; hmgr1 gene; RRII 105; Transgenic plants